Middle East illusions including peace in the Middle East? : reflections on justice and nationhood - Chomsky, Noam. (Lanham, MD : Rowman & Littlefield Publishers, 2003)
Discusses the history of the ongoing conflict between Israel and Palestine, the involvement of the United States in the peace process, and the changing face of terrorism in the twenty-first century.
Peace in the Middle East? -- The 1967 war and the 1970s -- Nationalism and conflict in Palestine -- A radical perspective -- Reflections on a national conflict -- The fourth round -- The peace movement and the Middle East -- Intifada, Israel and the United States at the turn of the millenium -- The "peace process" in U.S. global strategy -- The current crisis in the Middle East -- Prospects for peace in the Middle East -- al-Aqsa Intifada -- United States-Israel-Palestine -- 9-11 and the redeclared war on terror -- the "new age of terror."
Includes Index
Keywords: Arab-Israeli conflict -- 1993- -- Peace; Nationalism -- Palestine; Al-Aqsa Intifada, -- 2000-; United States -- Relations -- Israel; Israel -- Relations -- United States